Identifying Technological Trends and Promoting Strategies to Boost Innovation and Technology Transfer: A Case Study on the Patent Portfolio of Brazilian Public Research Institutions - Nestor Brandão Neto; Lester de Abreu Faria; Francisco Cristovão Lourenço de Melo (Journal of Aerospace Technology and Management, 2024)
The development of innovative technologies represents a fundamental pillar for economic and social progress in countries, and understanding the opportunities for utilizing these technological solutions is a critical success factor. The dynamics of the technology transfer (TT) process are determined by the peculiarities of factors related to both the consumer market and the business environment in which scientific and technological institutions (STIs) operate. In the aerospace and defense sector, technologies have high dual-use potential and interest various industrial sectors. This manuscript explores emerging trends and the potential for TT of the intellectual property (IP) portfolio of these STIs across a diversified spectrum of significant technological areas in the industrial sectors. It is a case study applied to public STIs, seeking to understand the trajectories of technological development and anticipate their impact on the Brazilian productive sector. This focus is relevant as it addresses critical aspects affecting research, development, and innovation (RD&I) in public STIs, which are all essential to deciphering the complexities of the contemporary technological innovation ecosystem. This study offers valuable insights for researchers and managers of RD&I and TT, highlighting the critical role of technology in understanding the dynamics of innovation and managing of RD&I in the sector in focus.